Evaluate the effectiveness of various diagnostic criteria and treatment outcomes in colposcopy screening for cervical cancer in a tertiary care medical college and hospital - Parveen, Umme; Nur, Ayesha Nigar; Chowdhury, Shahin R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Cervical cancer is a significant health concern, particularly in developing countries like Bangladesh. This study aimed to evaluate the efficacy of diagnostic criteria and treatment outcomes in cervical cancer screening using colposcopy. Methods: A retrospective study was conducted at Holy Family Red Crescent Medical College and Hospital, involving 110 female participants from January 2016 to December 2018. Inclusion criteria included women with symptoms such as vaginal discharge or postcoital bleeding, an unhealthy cervix or cervical erosion, abnormal Pap smear results, or positive VIA tests. Exclusion criteria were applied to ensure the integrity of the study. Results: The study included participants ranging from 20 to 60 years old. Among the age groups, individuals aged 31-40 were the most represented, accounting for 43% of the total population. The second largest group was those aged 20-30, comprising 29% of the participants. The mean and SD of the population is 27.5±14.36. The most prevalent reasons for referral were an unhealthy cervix (31%), white discharge (26%), and cervical erosion (18%). Other indications included post-coital bleeding (9%), abnormal Pap smear results (11%), positive results for VIA (3%) and HPV DNA (2%). LLETZ was performed in 6% of cases for the treatment of abnormal cervical cells, while EC was conducted in 18% of cases to collect tissue samples from the endocervical canal. Conclusions: The study highlights the importance of colposcopy in the screening process for cervical cancer, allowing for the detection of abnormalities and subsequent interventions. The findings contribute to the understanding of diagnostic criteria, treatment outcomes, and the need for early detection and prevention of cervical cancer.